2017
DOI: 10.1007/s00221-017-4957-9
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The effect of gamma-enhancing binaural beats on the control of feature bindings

Abstract: Binaural beats represent the auditory experience of an oscillating sound that occurs when two sounds with neighboring frequencies are presented to one’s left and right ear separately. Binaural beats have been shown to impact information processing via their putative role in increasing neural synchronization. Recent studies of feature-repetition effects demonstrated interactions between perceptual features and action-related features: repeating only some, but not all features of a perception–action episode hind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The focus on 40-Hz oscillations is in line with several reports about the positive effects of gamma-frequency BB. For example, 40-Hz BB improved working memory recall 27 , gamma-band BB impacted the control of visual feature binding 68 , and 40-Hz BB supported cognitive control of decision making 69 . Another study showed that 20-Hz BB improved long term memory while 5-Hz BB impaired memory compared to a white noise control condition 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The focus on 40-Hz oscillations is in line with several reports about the positive effects of gamma-frequency BB. For example, 40-Hz BB improved working memory recall 27 , gamma-band BB impacted the control of visual feature binding 68 , and 40-Hz BB supported cognitive control of decision making 69 . Another study showed that 20-Hz BB improved long term memory while 5-Hz BB impaired memory compared to a white noise control condition 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In order to develop a full picture of brain activity due to BB exposure, a suggestion would be that the application of other kinds of BB not used in this study such as alpha BB (Park et al, 2018;Shekar et al, 2018) or gamma BB (Colzato et al, 2017;Shekar et al, 2018). Additional studies that give an insight into brain signal modulation are needed for further understanding of which effects BB induces on humans.…”
Section: Future Workmentioning
confidence: 99%
“…These benefits were observed only in individuals with low rates of spontaneous blinking, which indicates low levels of dopamine in the striatum. Colzato et al 53 reported that 3-min 40 Hz binaural beats stimulation improved focus and attention in healthy young adults. Moreover, a study using 10-min 40 Hz stimulation in healthy adults 54 demonstrated that BWE acts by modeling specific brain oscillations, in cognitive processes sustained in the gamma wave frequency range, such as mental processes related to intelligence, self-control, and well-being.…”
Section: Main Findings Of the Studies Addressing The Effects Of Brain Waves On Mental Statesmentioning
confidence: 99%